Prioritizing Sex Recognition Over Learned Species Recognition: Hierarchical Mate Recognition in an Invasive Fish - Magellan, Kit; García-Berthou, Emili (Frontiers in Ecology and Evolution, 2021)
Mate recognition is the process of identifying and assessing the appropriate species, sex or population of another individual for their suitability as a potential mate. Recognition may be innate or learned. Learning, the acquisition of knowledge or skills through experience, involves a relatively long-term change in behavioural responses. In this study we examined learned and innate mate recognition in invasive male mosquitofish, Gambusia holbrooki, interacting with female conspecifics and male and female native toothcarp, Aphanius iberus. Male mosquitofish directed no mating attempts at male toothcarp whereas numerous attempts were made towards female toothcarp. Male mosquitofish therefore differentiated between males and females, but initially did not distinguish between con- and heterospecific females. Neither the presence of a male toothcarp, nor the presence of a refugia affected the number of mating attempts received by females. However, by the second day males appeared to learn to more accurately direct their mating attempts, with larger female mosquitofish receiving the most attention, though smaller toothcarp females were still harassed. We propose that male mosquitofish, with a coercive mating system, are selected for persistence despite rejection by potential mates. In this scenario, the pool of potential mates may include heterospecifics whose avoidance of mating attempts may be ignored by male mosquitofish. It may thus be adaptive for male mosquitofish to prioritise sex recognition over species recognition: if one sex is recognized as a “non-mate” this will cut 50% from the pool of potential mates whereas recognition of a single species will remove many fewer potential mates from the pool. This innate sex recognition together with rapid learning of species identity may be a factor in the invasive success of mosquitofish.